(untitled) (Veterinary Science, 2017)
Taxes on the agricultural professional activity and commercialization of beef, dairy products and grains in La Pampa province. As takes provoke a deep impact on taxpayers’ contribution, their effects in the veterinary profession as well as in beef, dairy products , grains and oilseeds were analyzed. Income tax, IVA, monotribute, tax of financial transference, all national taxes were evaluated the same as those referring to the province like gross income and stamp taxes. The importance of La Pampa agricultural emergency law in regard to payment prorogation an special rural credits was stated